Attacks on Indonesian police : not just terrorism? - Yang, Jennifer Hui. (2013)
Counterterrorism success overshadows the seeming inability of the police to win the hearts and minds of Indonesian society. It is important to understand the historical reasons for this distrust of the state's domestic or civil security apparatus. As such, it might be intime to replement meaningful policing reforms.